PERAN SUSTAINABILITY MEMEDIASI PENGARUH DEWAN KOMISARIS TERHADAP KINERJA KEUANGAN - JAUHARI, MOH. ALIYAN; HUSNAINI, WAHIDATUL; LENAP, INDRIA PUSPITASARI (GANEC SWARA, 2024)
This research empirically tests the direct and indirect influence of the number of board of commissioners on financial performance with the sustainability report (SR) as a mediating variable. The research sample was 157 data obtained from manufacturing companies listed on the Indonesia Stock Exchange and disclosed sustainability reports for the 2019-2021 period. Hypothesis testing uses path analysis. The test results show that the number of board of commissioners and sustainability reports do not directly influence financial performance, while the number of board of commissioners directly influences the disclosure of sustainability report. Sustainability reports cannot mediate the influence of the number of board of commissioners on financial performance, because SR is still voluntary so not many companies disclose it